Amplificação sonora em bebês: Mensuração da diferença individual entre a orelha e o acoplador de 2cc (RECD) - Campos, Fernanda Marcon do Amaral (2007)
Objective: The purpose of this study was to investigate two methods for obtaining the real-ear to coupler difference (RECD) in infants: with an insert earphone and the measure in free field with a linear hearing aid. The test -retest reliability and reproducibility of both methods were compared as well as the reliability of between-ear RECD measures. The values of RECD obtained were compared with the database of DSL [i/o] 4.1 and 5.0. Design: The RECD was measured in 25 hearing impaired infants aged 3 months to 24 months with no malformations or visible syndrome and with normal middle ear function. The RECD values were obtained via both methods twice each with removal and reinsertion of the probe microphone between each measure and using the infant s earmold. Results: The insert earphone method resulted in significantly better test-retest reliability than the free field because the values were most similar for all frequencies and ages. The RECD values obtained in the current study were similar to those proposed by DSL [i/o] 4.1 and DSLm 5.0 database. There were no significant differences between the mean RECDs obtained using an insert earphone compared with those obtained via free field method but the standard deviation is significantly higher in free field measurement. Conclusions: The results of this study support the use of the insert earphone method of measurement of the RECD as a reliable tool in assisting with the hearing aids fitting in infants. The variability is smaller in this method and the values were more similar to DSL[ i/o] 4.1 and DSLm 5.0 database